Competencias emocionales y el desorrollo integral en los estudiantes de 9° año de educación básica superior de la unidad educativa replica Eugenio Espejo en el cantón Babahoyo provincia de los Ríos. - Macías Lemus, Vanessa Alexandra (2017)
The present investigation has like objective describe the different classes of emotional competitions and arrive at a suitable theoretical position that must be applied to fortify the emotional competitions and integral development in the students of the 9º Year of Superior Basic Education of the Educational Unit "Replica Eugenio Mirror "of Babahoyo canton, province of Los Rios. In order to achieve a comprehensive education that includes knowledge that includes skills, abilities and skills for an improvement in their behavior and attitudes in achieving full and active human beings. Emotional competencies are a very important aspect that has active, effective and responsible citizenship. Its acquisition and dominance favors a better adaptation to the social context and a better confrontation to the challenges posed by life. Among the aspects that are favored by emotional competences are learning processes, interpersonal relationships, problem solving and the achievement of a job, etc. A survey and questionnaire was made to the total universe of the population, tabulation and interpretation of data provided the recommendations and conclusions, the result obtained gave way to the proposal to solve the problem, which is a didactic guide for the educational psychologist to guide to teachers and students, which allow the best development of emotional education in students.